Comparison of band structure and superconductivity in FeSe0.5Te0.5 and FeS - 杨阳;冯世全;向圆圆;路洪艳;王万胜 (中国物理B：英文版, 2017)
The isovalent iron chalcogenides, FeSe0.5Te0.5 and FeS, share similar lattice structures but behave very differently in superconducting properties. We study the underlying mechanism theoretically. By first principle calculations and tight-binding fitting, we find the spectral weight of the dX2-Y2 orbital changes remarkably in these compounds. While there are both electron and hole pockets in FeSe0.5Te0.5 and FeS, a small hole pocket with a mainly dX2-Y2 character is absent in FeS. We find the spectral weights of dX2-Y2 orbital change remarkably, which contribute to electron and hole pockets in FeSe0.5Te0.5 but only to electron pockets in FeS. We then perform random-phase-approximation and unbiased singular-mode functional renormalization group calculations to investigate possible superconducting instabilities that may be triggered by electron-electron interactions on top of such bare band structures. For FeSe0.5Te0.5, we find a fully gapped s-wave pairing that can be associated with spin fluctuations connecting electron and hole pockets. For FeS, however, a nodal dxy （or dx2-y2 in an unfolded Broullin zone） is favorable and can be related to spin fluctuations connecting the electron pockets around the corner of the Brillouin zone. Apart from the difference in chacogenide elements, we propose the main source of the difference is from the dX2-Y2 orbital, which tunes the Fermi surface nesting vector and then influences the dominant pairing symmetry.